The Permits as an Integration Mechanism: Legal Protection Efforts for Land Rights Holders Relating to Mining Permits - Surahman Surahman; Nurhayati Mardin; Syachdin Syachdin; Widyatmi Anandy (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
This research aims to analyze the position of permits as well as formulate the position of permits as an integration mechanism related to preventive means to minimize disputes and disputes between mining permit holders. This research is normative legal research with a statutory and conceptual approach. The research results confirm that the position of permits as a preventive legal protection effort in society has an orientation to prevent and minimize disputes or disputes between land rights and mining permits. Permits as an integration mechanism for land rights holders relating to mining permits can be carried out by carrying out reformulation in which mining permits are granted by first fulfilling the conditions for resolving various problems between mining permit holders and land right holders. Resolving various problems between mining permit holders and land rights holders is carried out using a comprehensive and holistic approach that not only prioritizes legal approaches, but accommodates political, economic and cultural approaches.